Drought-linked resource limitations on the body condition of a large ungulate - Brown, Casey L.; Nielson, Ryan M.; Clark, Darren; Kennedy, Ryan; Loonam, Kenneth; Rowland, Mary M.; Wisdom, Michael J. (Frontiers in Ecology and Evolution, 2025)
Understanding how indirect effects of climate can interact with density-dependent processes has become increasingly important as variability changes resource availability for wildlife. Both climate and animal density can drive the abundance of vegetation and control the degree of competition for forage between ungulates. Further, climate-density relationships may be more pronounced for females in the population as they may need to compensate nutritionally for the energetic costs of raising young. Quantifying the effects of these relationships on individual animal performance is challenging because it requires long-term data that spans changing densities and climatic patterns to observe the mechanisms in play. Our objectives were to: 1) evaluate differences in fall (Nov–Dec) female elk body condition based on lactation status; 2) assess the relationships between seasonal bottom-up covariates, elk density, and changes in elk body fat; and 3) examine the timing of growing season conditions associated with variation in elk body fat. We used a 20-year dataset of female elk (Cervus canadensis) across varying population densities and seasonal bottom-up patterns to quantify changes in body fat in a semi-arid forested rangeland system in northeastern Oregon, USA. Body fat of lactating elk was negatively associated with severe drought at higher elk densities. Body fat of lactating elk was greater following wet summers with a later green-up date. Higher precipitation during the growing season significantly increased body fat for all groups of elk. These results collectively support the importance of the indirect, bottom-up effects on female elk nutrition. If summer drought continues to increase in duration and intensity in the Pacific Northwest, USA, we expect to see declines in elk body condition with potential impacts to population-level performance.